IL17A-mediated endothelial breach promotes metastasis formation - Kulig, Paulina; Gorzelanny, Christian (Cancer immunology research, 2016)
The role of the IL23/IL17A axis in tumor-immune interactions is a matter of controversy. Although some suggest that IL17A-producing T cells (TH17) can suppress tumor growth, others report that IL17A and IL23 accelerate tumor growth. Here, we systematically assessed the impact of IL17A-secreting lymphocytes in several murine models of tumor lung metastasis. Genetic fate mapping revealed that IL17A was secreted within lung metastases predominantly by γδ T cells, whereas TH17 cells were virtually absent. Using different tumor models, we found Il17a-/- mice to consistently develop fewer pulmonary tumor colonies. IL17A specifically increased blood vessel permeability and the expression of E-selectin and VCAM-1 by lung endothelial cells in vivo. In transgenic mice, specific targeting of IL17A to the endothelium increased the number of tumor foci. Moreover, the direct impact of IL17A on lung endothelial cells resulted in impaired endothelial barrier integrity, showing that IL17A promotes the formation of lung metastases through tumor-endothelial transmigration.
Gesehen am 18.10.2019
Published online first November 19, 2015